Development and evaluation of a seed extractor for ash gourd and cucumber - ANEESH MOHAN; Dr. Santhi Mary Mathew (Guide) (Tavanur 2012 DEPARTMENT OF POST HARVEST TECHNOLOGY AND AGRICULTURAL PROCESSING)
Development and evaluation of a seed extractor for ash gourd and cucumber
Development and evaluation of a seed extractor for ash gourd and cucumber